Trends of Injuries due to Gender Based Violence, Uganda, 2012 – 2016, a retrospective descriptive analysis - Biribawa, Claire; Nuwemastiko, Rebecca; Oporia, Frederick; Baguma, Ezekiel; Bulage, Lilian; Okethwangu, Denis; Ario, Alex Riolexus; Kobusingye, Olive (African Field Epidemiology Network, 2020)
Context: Child obesity, one of the major contributors to noncommunicable diseases in developing countries, is rising following drastic economic growth and lifestyle changes. In Uganda, noncommunicable diseases as a cause of death have increased from 15% in 1990 to 35% in 2019. Aim: The study aimed to investigate schoolchildren’s obesity status, lifestyle behaviors, and the factors of obesity in urban Uganda. Methods: The study was conducted with a cross-sectional, descriptive quantitative design. The survey using the researcher-developed questionnaire and physical measurement tools for 330 children aged 9 to 11 years old in 6 elementary schools in urban Uganda in November 2018. The Japanese Red Cross College of Nursing Institutional Review Board approved this study (Approval Number: 2018-066). Results: Obesity status among schoolchildren in urban Uganda was 67.6% normal, 25.2% underweight, 5.4% overweight, and 1.8% obese. Conclusion: Obesity and overweight have not been predominant in this population. However, children's growth must be carefully monitored to prevent future overweight and obesity due to the limited availability of school health services and rapid lifestyle changes. Demographic factors associated with obesity status (waist-hip ratio, body fat, and body mass index) were gender, financial access to food, screen time, sleep time